Taiwan and the People's Republic of China foes or partners? - Axel J. Halbach (Intereconomics, 1979)
Taiwan is developing ever more perceptibly into what both Peking and Taipei consider it to be: a province of China, albeit a province sui generis—part of China and yet an independent state, enjoying world-wide recognition though denied diplomatic relations, a leading commercial power but without proper commercial treaties. The prosperity which has been generated in the island is an ever present temptation for the People's Republic. Is it tempting enough to provoke an appeal to arms? Or is Red China's perfectly legitimate interest directed primarily at the exchange of goods and technologies?
Keywords: 330; China